Magnetic swirls and associated fast magnetoacoustic kink waves in a solar chromospheric flux tube - Murawski K.; Kayshap P.; Srivastava A.K.; Pascoe D.J.; Jelínek P.; Kúzma B.; Fedun V. (My University, 2025)
We perform numerical simulations of impulsively generated magnetic swirls in an isolated flux tube that is rooted in the solar photosphere. These swirls are triggered by an initial pulse in a horizontal component of the velocity. The initial pulse is launched either (a) centrally, within the localized magnetic flux tube or (b) off-central, in the ambient medium. The evolution and dynamics of the flux tube are described by three-dimensional, ideal magnetohydrodynamic equations. These equations are numerically solved to reveal that in case (a) dipole-like swirls associated with the fast magnetoacoustic kink and m = 1 Alfvén waves are generated. In case (b), the fast magnetoacoustic kink and m = 0 Alfvén modes are excited. In both these cases, the excited fast magnetoacoustic kink and Alfvén waves consist of a similar flow pattern and magnetic shells are also generated with clockwise and counter-clockwise rotating plasma within them, which can be the proxy of dipole-shaped chromospheric swirls. The complex dynamics of vortices and wave perturbations reveals the channelling of sufficient amount of energy to fulfil energy losses in the chromosphere (~104 Wm-1) and in the corona (~102 W m-1). Some of these numerical findings are reminiscent of signatures in recent observational data. © 2016 The Authors.